2017
DOI: 10.2169/internalmedicine.6754-15
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Regression of Epithelioid Angiosarcoma in a Young Woman

Abstract: A 20-year-old Japanese woman with a history of pulmonary atresia was referred to our hospital after the detection of an abnormal mass in the right lung and mediastinal lymphadenopathy. A cytological specimen obtained by transbronchial brushing indicated that the pathological diagnosis was non-small cell lung cancer. During the follow-up period, the tumor spontaneously regressed. At four months after the diagnosis, she experienced sudden bleeding from the small intestine. The histological characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, 21 reports have been published since 1990. The pathological diagnoses in these cases varied, including 3 cases each of angiosarcoma 9-11 and osteosarcoma 12,13 ; 2 cases each of extraskeletal osteosarcoma 14,15 , leiomyosarcoma 16,17 , epithelioid angiosarcoma 18,19 , and chordoma 20,21 ; and 1 case of chondrosarcoma 22 , extraskeletal myxoid chondrosarcoma 23 , fibrosarcoma 24 , infantile fibrosarcoma 25 , myxofibrosarcoma 26 , alveolar soft part sarcoma 27 , and synovial sarcoma 28 . Thus, there is no specific pathological diagnosis that tends to exhibit SR (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, 21 reports have been published since 1990. The pathological diagnoses in these cases varied, including 3 cases each of angiosarcoma 9-11 and osteosarcoma 12,13 ; 2 cases each of extraskeletal osteosarcoma 14,15 , leiomyosarcoma 16,17 , epithelioid angiosarcoma 18,19 , and chordoma 20,21 ; and 1 case of chondrosarcoma 22 , extraskeletal myxoid chondrosarcoma 23 , fibrosarcoma 24 , infantile fibrosarcoma 25 , myxofibrosarcoma 26 , alveolar soft part sarcoma 27 , and synovial sarcoma 28 . Thus, there is no specific pathological diagnosis that tends to exhibit SR (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…The main clinical features included gastrointestinal bleeding (black stool, hematochezia or occult bleeding), abdominal discomfort/pain, and abdominal mass. Other symptoms included intestinal obstruction, diarrhea and weight loss, nausea/vomiting, acute abdomen,bowel perforation,skin pallor/ anemia, etc [2][3][4][5][6][7][8]. Some early cases were even asymptomatic and were occasionally found in routine endoscopy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis in advanced diseases is very poor despite the use of surgery, chemotherapy and even radiotherapy. Surprisingly, there is a case of spontaneous regression of pulmonary metastatic EAS from the small intestine [5]. Abdominal CT showed that the intestinal wall of the upper jejunum was thickened near the duodenum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported number of spontaneous regressions varies widely depending on the type of cancer, with large number of reports in renal cell cancer, malignant melanoma and lymphoma [5]. Although the mechanism behind spontaneous regression is unknown, it has been hypothesized as due to influence of hormone, involvement of immune modulation, trauma, blood flow disorder, infection and emergence of paraneoplastic syndrome [6, 7]. Among the various possibilities, enhancement of the immune system has been suggested to play an important role in both the progression and regression of cancers.…”
Section: Discussionmentioning
confidence: 99%